Adaptive Method Using Controlled Grid Deformation - Florin FRUNZULICA (INCAS Bulletin, 2011)
The paper presents an adaptive method using the controlled grid deformation over an elastic, isotropic and continuous domain. The adaptive process is controlled with the principal strains and principal strain directions and uses the finite elements method. Numerical results are presented for several test cases.